ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANGAN PADA PT. DAYA ANUGRAH MANDIRI CABANG MANADO - Kawatu, Brenda Meydita Lineke; Tinangon, Jantje J.; Gerungai, Natalia Y. T. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Inventory is one of the important assets of the company. Therefore, internal control over inventory is needed to protect against the risk of theft, damage and fraud. This study aims to determine the internal control system for merchandise inventory implemented by PT. Daya Anugrah Mandiri Manado Branch in terms of the internal control component according to the coso (committee of sponsoring organizations). The method of analysis in this study uses qualitative methods by obtaining data through interviews and documentation and then conclusions are drawn. The results showed that the internal control system for merchandise inventory applied by PT. The overall grace of the Manado branch of Anugrah is already good. Companies should further enhance the security of inventory in the warehouse by installing cctv camera so that security is more secure, and the need for an accounting department that is specifically tasked with carrying out financial records and reporting.